Voting with your wallet? Municipal budget policy and election results - Stijn Baert; Herman Matthijs; Ilse Verdievel (Kiel Institute for the World Economy (IfW), 2018)
In this paper, the authors examine the impact of municipal budget policy on the percentage of votes for the incumbent majority parties in subsequent elections. They contribute to the academic literature by examining the combined influence of taxes, expenditures and debt. Based on data for Flanders (Belgium) between 1994 and 2012, they find no significant association between these budget variables and the actual election results.
Keywords: D72; E62; H71; H72; P48; R50; 330; budget policy; municipal elections; yardstick voting; political economics